Effects of Yoga on Blood Glucose and Lipid Profile of Type 2 Diabetes Patients Without Complications: A Systematic Review and Meta-Analysis - Shanshan Chen; Shilin Deng; Yang Liu; Tiantian Yin (Frontiers Media S.A., 2022)
BackgroundType II diabetes mellitus (T2DM) has become a worldwide public health problem. Although it has been empirically established that physical activity is a promising therapeutical approach to the prevention and management of T2DM, the effectiveness of yoga on T2DM has not yet reached an agreement across studies and also needs an updated synthetic examination.PurposeThe purpose of this study was to examine the effect of yoga training on diabetes-related indicators compared with usual care.MethodsThe review protocol of this study has been registered in the PROSPERO with a registration number CRD42021267868. A systematic literature search through electronic databases was conducted to identify yoga-based intervention (i.e., randomized controlled trial [RCT]; e.g., yogic postures, movements, breathing, and meditation) studies reporting outcomes on glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), postprandial blood glucose (PPBG), total cholesterol (TC), triglycerides (TG), and body mass index (BMI). A number of two researchers manually reviewed and assessed each article using the Cochrane Risk of Bias Tool 2.0. The literature search identified 296 eligible entries, of which 13 were finalized after screening using predefined inclusion and exclusion criteria. The extracted data (group mean and standard deviation at posttest) were synthesized using random-effects meta-analyses. Finally, potential moderators were explored using subgroup analysis and sensitivity analysis.ResultsThe standardized mean difference for the effects of yoga was significant on HbA1c (MD = −0.47; 95%CI: −0.77, −0.16; Z = 3.02, p = 0.003), FBG (SMD = −0.92; 95%CI: −1.55, −0.29; Z = 2.87, p = 0.004), PPBG (SMD = −0.53; 95%CI: −0.86, −0.21; Z = 3.20, p = 0.001), and TG (SMD = −0.32; 95%CI: −0.54, −0.10; Z = 2.86, p = 0.004). However, yoga effect was not observed on TC (SMD = −0.84; 95%CI: −1.71, 0.04; Z = 1.87, p = 0.06) and BMI (MD = −0.63; 95%CI: −1.42, 0.16; Z = 1.57, p = 0.12).ConclusionThe findings suggest that yoga can improve the biochemical indices of blood glucose and the lipid profile of patients with T2DM. Therefore, yoga can be prescribed as an effective and active complementary treatment for T2DM. However, this study only tested yoga as a short-term treatment. In the future, rigorous RCTs with a larger sample size may be carried out to examine the long-term effect of yoga on T2DM.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=267868, identifier: CRD42021267868.